Menacing Menas? Saint Menas as a Military Saint and Divine Trickster in his Greek Miracle Collection (BHG 1256-1269) - Doroszewska, Julia; Doroszewski, Filip (Vox Patrum, 2025)
This study examines the Greek miracle collection of Saint Menas (BHG 1256–1269), investigating the literary construction of the saint as both a military protector and a divine trickster. The analysis highlights the inconsistencies in Menas’s portrayal, contrasting his literary depiction as a mounted avenger with non-literary evidence that emphasizes his role as a healer. Using comparative hagiographic analysis, the paper explores the influence of late antique principles of decorum, which shaped depictions of saints to avoid direct violence. The study delves into Menas’s punitive and protective miracles, analyzing their reliance on humour, trickery, and indirect retribution rather than overt combat. These narratives are contextualized within the broader framework of military saints, including Theodore, Demetrios, and Phoibammon, whose miracles also embody justice and protection through divine intervention. This paper reveals how such portrayals reflect evolving Christian attitudes toward violence, sanctity, and the supernatural. The findings contribute to the understanding of late antique religious imagination, showcasing how narrative ingenuity addressed both theological and societal needs in Christian antiquity.